2005
DOI: 10.1093/annhyg/mei045
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Contamination with Cytotoxic Drugs in Healthcare Using Positive Air Pressure Isolators

Abstract: Occupational exposure to cytotoxic drugs of hospital personnel involved in their preparation and administration is a major issue: ever since the introduction of protective measures in recent decades, the handling of these drugs has always been referred to as an occupational health hazard. Isolator technology was one of the protective equipments aimed at providing safe handling, but it has not yet been studied regarding contamination. The present study evaluates surface contamination with four cytotoxic drugs [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Several previous studies have examined hand exposure to antineoplastic drugs, mainly cyclophosphamide. A previous trial from the Netherlands by Fransman et al (2007) found considerable actual hand exposure in nurses and in pharmacy technicians and cleaning personnel, which was later substantiated by Italian (Turci et al 2003), French (Crauste-Manciet et al 2005), and Canadian (Hon et al 2014) studies measuring contamination of used gloves or hands. Cleaning personnel, especially, could potentially be at risk, as several studies showed high levels of contamination on floors of both the pharmacy as well as wards and patient toilets (Hedmer et al 2008;Connor et al 2010;Fleury-Souverain et al 2015;Chauchat et al 2019).…”
Section: Introductionmentioning
confidence: 87%
“…Several previous studies have examined hand exposure to antineoplastic drugs, mainly cyclophosphamide. A previous trial from the Netherlands by Fransman et al (2007) found considerable actual hand exposure in nurses and in pharmacy technicians and cleaning personnel, which was later substantiated by Italian (Turci et al 2003), French (Crauste-Manciet et al 2005), and Canadian (Hon et al 2014) studies measuring contamination of used gloves or hands. Cleaning personnel, especially, could potentially be at risk, as several studies showed high levels of contamination on floors of both the pharmacy as well as wards and patient toilets (Hedmer et al 2008;Connor et al 2010;Fleury-Souverain et al 2015;Chauchat et al 2019).…”
Section: Introductionmentioning
confidence: 87%
“…The risks associated with occupational exposure to antineoplastic drugs can be genotoxic effects or a decrease in reproductive functioning [ 3 , 4 ]. Several sources of contamination have been determined in hospital settings: in pharmacies, notably on the external surface of commercial vials [ 5 ], during the compounding process [ 6 ], inside isolators [ 7 ] and in medical wards (e.g. preparations coming from the pharmacy and patients’ excreta) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For 5-FU, we found a maximum concentration of 2.15 ng/cm² on gloves. While some authors reported values well below this concentration (0.018-0.33 ng/cm²), others reported concentrations high above these values (449.3 and 11.4 ng/cm²) (26,27,36,41). In total, 10 samples were analyzed from PPE (masks and gloves).…”
Section: Discussionmentioning
confidence: 99%